Factor Analysis of E-Learning Acceptance in SMK Sore Tulungagung Using Technology Acceptance Model (TAM) - Rhohmah Indah; Eristya Maya Safitri; Tri Puspa Rinjeni (Jurnal Riset Informatika, 2025)
Although the use of E-Learning has been expanded as a modern learning solution, its implementation at SMK SORE Tulungagung still faces obstacles such as low student participation, difficulty in accessing E-Learning features, and delays in submitting assignments. This indicates that there are obstacles in the acceptance of learning technology by students. This study aims to analyze the factors that influence the acceptance of E-Learning using the Technology Acceptance Model (TAM) framework with the main variables: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), Behavioral Intention to Use (BIU), and Actual Use (AU). The method used is quantitative with a predictive approach, data was obtained by distributing questionnaires to students majoring in Computer and Network Engineering, Data analysis was carried out using validity, reliability, and structural modeling (SEM-PLS) tests. The results showed that PU and PEOU significantly influenced students' attitudes and intentions in using E-Learning. In addition, BIU contributed to the use of the actual system and external factors such as complexity and voluntariness were also analyzed to determine the indirect effect on technology acceptance.